Sustainability Analysis of Waste Management in Kupang City Using MDS Rapfish Analysis - Handrianus Josef Hae Jami; Alfred O. M. Dima; Roddialek Pollo (Publikasi Indonesia, 2025)
The research on the sustainability of waste management in the city of Kupang aims to analyze the current status of waste management sustainability in the city. The primary objective of this study is to evaluate the sustainability status of the waste management system and identify the factors that influence its sustainability. This research employs sustainability analysis using the Multi-Dimensional Scaling (MDS) technique through the RAPFISH (Rapid Assessment Technique for Fisheries) approach. The data collection techniques in this study include observation, Questionnaires, and Interviews. Field data collection will be conducted from July to November 2023. The research results indicate that the waste management system in Kupang City, in terms of reduction and handling, is not optimal, with a sustainability status of waste management in Kupang City having an average index value of 46.17, placing it in the 'Less Sustainable' category. The conclusion of this study emphasizes that waste management in Kupang City still requires improvement, particularly in terms of regulations, facility and infrastructure enhancements, and community engagement. The implications of this study are the need to transition the landfill system from open dumping to a sanitary landfill, enhance education and socialization programs, and allocate a larger budget for more sustainable waste management.